Strategic Objectives For Developing The Banking Sector And The Expected Role In Enhancing Economic Growth In Iraq (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract: There is no doubt that there is an anticipated role through working on developing the Iraqi banking sector, as any reform of this sector means an active and contributing role in sustainable development. This is a vital goal for all the strategies set by the Central Bank of Iraq, especially since there is a structural defect in the composition of the monetary mass of the Iraqi economy, as 80% of this mass is outside the Iraqi governmental and private banking system. Herein lies the importance of this research in studying and analyzing the strategic objectives for developing the banking sector and the anticipated role in promoting economic growth by activating the function of this sector in collecting local savings and granting them to income-generating productive, economic and service projects. It is worth noting that the contribution of the Iraqi banking sector is small compared to neighboring countries, for example, as it does not exceed 2%, while Jordan is 8%. It is hoped that this percentage will increase in light of the measures and reforms of the Central Bank of Iraq in increasing financial liberalization and increasing financial allocations and loans granted to private sector projects.Keywords: Strategic objectives, banking sector, economic growth .